Analyzing the Influence Factors on Brand Image - Wang, Zixi (Transactions on Economics, Business and Management Research, 2024)
In the context of the "socialite" rebranding initiative, MIU MIU has successfully experienced a renewed sense of vitality. The purpose of this study was to explore what factors led to the concept of rebranding and why this action can be successful for MIU. This paper uses social identity theory, brand association theory, and brand positioning theory to carry out relevant analysis. The final analysis of brand re-shaping due to changes in consumer groups, widespread social media communication, and market trends suggests that the future should be appropriate to broaden the audience, regardless of age: more people who want to be "socialites" have the opportunity to buy, advertise on social media, collaborate with more stars, and upload the brand ambassador’s clothes to attract more consumers. The brand can also use unique colors to express brand style, adding brand memory points and at the same time creating a unique style that is unique to MIU MIU. The value of such a study is to provide ideas for more brands to achieve brand image rebranding and improve the lack of papers on MIU MIU brand research.